Mulheres migrantes : trajetórias de venezuelanas em Boa Vista - RR - Oliveira, Viviane Lima de Almeida (2020)
Writing about people's life trajectories requires considering subjective and social aspects with equal importance, therefore, it requires emphasizing that, although they are distinct, these aspects are articulated and one does not exist without the other. In other words: there is no society without subjects nor subjects without society. This work aims to analyze the female migration carried out by Venezuelans to Boa Vista, Roraima, trying to understand what makes a person leave their place of origin and migrate to an indefinite place, requiring to understand which positive and negative points involved this decision and experience in the new territory of Boa Vista. Qualitative interviews were conducted with four migrant women, who were living in the space located around the International Highway of Boa Vista-RR. It is these women, their strengths and their dilemmas that I have sought to know. As a result of the research, it was possible to know their life trajectory, what made them decide to migrate, what their lives were like at the place of departure and how their lives are at the provisional place of arrival, the transformations experienced by them sprang up in them a strength they did not even imagine they had so that they could face the setbacks encountered during the migratory journey, the adversities they had and have to continue to face, either at the place of departure or at the provisional place of arrival.